Relationships among field-test measures and physical match performance in elite-standard soccer referees - Weston, M.; Castagna, C.; Helsen, W. F.; Impellizzeri, F. (Journal of Sports Sciences, 2009)
The aim of this study was to assess the extent to which measures derived from the new FIFA referees' fitness tests can be used to monitor a referee's match-related physical capacity. Match-analysis data were collected (Prozone®, Leeds, UK) from 17 soccer referees for 5.0 (s = 1.7) FA Premier League matches per referee during the first 4 months of the 2007-08 season. Physical match performance categories included total distance covered, high-intensity running distance (speed >5.5 m · s-1), and sprinting distance (>7.0 m · s-1). The two tests were a 6 40-m sprint test and a 150-m interval test. Heart rate demand was correlated with total match distance covered (r = -0.70, P = 0.002) and high-intensity running (r = -0.57, P = 0.018) in the interval test. The fastest 40-m sprint was related to total distance covered (r = -0.69, P = 0.002), high-intensity running (r = -0.76, P < 0.001), and sprinting distance (r = -0.75, P = 0.001), while mean time for the 40-m sprints was related to total distance covered (r = -0.70, P = 0.002), high-intensity running (r = -0.77, P < 0.001), and sprinting distance (r = -0.77, P < 0.001). The referees who recorded the best interval-test heart rate demand and fastest 40-m time produced the best physical match performances. However, only the sprint test and in particular the fastest 40-m time had appropriate construct validity for the physical assessment of soccer referees.